2015
DOI: 10.1007/s10811-015-0559-8
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of shear stress sensitive and tolerant microalgal species in a tubular photobioreactor equipped with a centrifugal pump

Abstract: The tolerance to shear stress of Tetraselmis suecica, Isochrysis galbana, Skeletonema costatum, and Chaetoceros muelleri was determined in shear cylinders. The shear tolerance of the microalgae species strongly depends on the strain. I. galbana, S. costatum, and C. muelleri exposed to shear stress between 1.2 and 5.4 Pa resulted in severe cell damage. T. suecica is not sensitive to stresses up to 80 Pa. The possibility to grow these algae in a tubular photobioreactor (PBR) using a centrifugal pump for recircul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…These studies indicated that microalgal biomass cultivation is predominantly affected by two fluid dynamic factors; shear stress and liquid mixing . While rapid mixing of liquid cultures along the direction of light transmission can improve the overall light utilization, thereby enhancing photosynthetic efficiencies, it also induces intense shear stresses that can severely damage algal cells resulting in biomass death …”
Section: Introductionmentioning
confidence: 99%
“…These studies indicated that microalgal biomass cultivation is predominantly affected by two fluid dynamic factors; shear stress and liquid mixing . While rapid mixing of liquid cultures along the direction of light transmission can improve the overall light utilization, thereby enhancing photosynthetic efficiencies, it also induces intense shear stresses that can severely damage algal cells resulting in biomass death …”
Section: Introductionmentioning
confidence: 99%
“…It is important for us to know if or not the shear stress is limited to levels that can be tolerated by the microalgae, since hydrodynamic forces evoked by excessive turbulent mixing in closed TPBRs may limit the application of these systems, as described in the study of Michiel et al . In order to investigate the influence of the built‐in helical rotors on hydrodynamic forces, the max shear stress and the average shear stress were calculated from simulation in this work.…”
Section: Equipment and Methodsmentioning
confidence: 99%
“…The friction velocity can be expressed as follows (Leupold et al, ; Michels et al, ): Ufgoodbreakinfix=true(τsρltrue)1/2where Uf is the friction velocity (cm/s), and τs is the shear stress (Pa). A friction velocity higher than 1 cm/s damages C. reinhardtii cells and decreases their photosynthetic efficiencies (Leupold et al, ; Michels et al, ). The decrease in the photosynthetic efficiency caused by high friction velocity (>1 cm/s) reduces the PBR productivity.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…However, microalgal cells are sensitive to fluid dynamic stresses. Intensive mixing can cause shear‐induced damage to these cells and consequently reduce their biomass productivity (Leupold, Hindersin, Gust, Kerner, & Hanelt, ; Michels, van der Goot, Vermuë, & Wijffels, ; Thomas & Gibson, ). In addition to the bubble rising and bursting phenomena in the PBR, the bubble formation at the sparger could also damage algal cells (Barbosa, Hadiyanto, & Wijffels, ).…”
Section: Introductionmentioning
confidence: 99%